Integrative analysis of scRNA-seq and scATAC-seq revealed transit-amplifying thymic epithelial cells expressing autoimmune regulator - Takahisa Miyao; Maki Miyauchi; S Thomas Kelly; Tommy W Terooatea; Tatsuya Ishikawa; Eugene Oh; Sotaro Hirai; Kenta Horie; Yuki Takakura; Houko Ohki; Mio Hayama; Yuya Maruyama; et al. (eLife, 2022)
Medullary thymic epithelial cells (mTECs) are critical for self-tolerance induction in T cells via promiscuous expression of tissue-specific antigens (TSAs), which are controlled by the transcriptional regulator, AIRE. Whereas AIRE-expressing (Aire+) mTECs undergo constant turnover in the adult thymus, mechanisms underlying differentiation of postnatal mTECs remain to be discovered. Integrative analysis of single-cell assays for transposase-accessible chromatin (scATAC-seq) and single-cell RNA sequencing (scRNA-seq) suggested the presence of proliferating mTECs with a specific chromatin structure, which express high levels of Aire and co-stimulatory molecules, CD80 (Aire+CD80hi). Proliferating Aire+CD80hi mTECs detected using Fucci technology express a minimal number of Aire-dependent TSAs and are converted into quiescent Aire+CD80hi mTECs expressing high levels of TSAs after a transit amplification. These data provide evidence for the existence of transit-amplifying Aire+mTEC precursors during the Aire+mTEC differentiation process of the postnatal thymus.